Group Facial Width-to-Height Ratio Predicts Intergroup Negotiation Outcomes - Yang, Yu; Tang, Chen; Qu, Xiaofei; Wang, Chao; Denson, Thomas F. (Frontiers in Psychology, 2018)
Past studies have found that the facial width-to-height ratio (FWHR) is associated with a range of traits and behaviors that are possibly important to dyadic negotiations. However, it is unknown whether the FWHR would have an impact on intergroup negotiations, which happen frequently and often have higher stakes in the real world. To examine this question, in the current study, we randomly assigned 1,337 Chinese business executives into 288 groups and they completed a multi-issue negotiation exercise against each other. Results showed that groups with larger maximum individual FWHRs achieved objectively better negotiation outcomes. We conclude that groups containing individuals with relatively large FWHRs can claim more value in negotiations between groups.